The Effect of Job Insecurity on Employee Service Innovative Behavior at Axana Hotel Padang - Adek Kurnia Fiza; Arif Adrian (JURNAL PENDIDIKAN DAN KELUARGA, 2022)
The purpose of this research is to test the effect job insecurity on innovative work behavior at Axana hotel Padang. The sampling method used purposive sampling with 35 employees. The data analysis in this research used a descriptive statistical test method, derivative tests including validity and reliability, and hypothesis testing. The tool used to test in this research used SPSS 25. The result of this research show job insecurity positively relates to innovative work behavior.